The integration of Dick and Carey model in developing potrait teaching kit for visual art education teachers / Nor Syamimi Samsudin - Samsudin, Nor Syamimi (2014)
This study was aimed at developing the teaching aids to be utilized in Visual Art Education classrooms. Portrait is the most difficult lesson to teach as it involves tedious process and highly-skilled procedure (Opie, 2003). A teaching kit for teaching portrait lesson (Portrait Teaching Kit) was developed; integrating Dick and Carey Model (2005) as to prepare the instructional technology as the alternative in teaching portrait among teachers. This study was identified the VAE teachers’ perception and motivation towards Portrait Teaching Kit as the teaching aid in VAE subject. A descriptive survey research was employed as to collect all the data. In this study, the respondents chosen were 30 experienced teachers of VAE subject among selected secondary school in Kuala Kangsar, Perak. Based on the findings, the study shown that implementation of Portrait Teaching Kit in VAE subject can provided new ideas and knowledge and enhanced VAE teachers’ perception and motivation to delivering portrait lesson in the classroom. It is hoped that the Portrait Teaching Kit can facilitate portrait lesson among VAE.